The family system resulting from the union between the Malawi men, working at the Zebediela estates with South African born Bantu women with special reference to the roles of the various family members - Mabudafhasi, Dinani E. (University of Limpopo, 1973)
Refer to the document
Thesis (M. A. (Sociology)) University College of the North, 1973
Keywords: Family system; Malawi men; South African bantu women; Marriage and Family -- South Africa -- Lebowa